Pre-Term Pre-Labor Rupture of Membranes and the Role of Amniocentesis - Abi Nader, Khalil (2010)
Pre-labour premature rupture of membranes (PPROM) is defined as rupture of membranes more than 1 hour prior to the onset of labour at <37 weeks gestation. PPROM occurs in approximately 3% of pregnancies and is responsible for a third of all preterm births. Once membranes are ruptured prolonging the pregnancy has no maternal physical advantage but fetal morbidity and mortality are improved daily at early gestations: 19% of those infants born <25 weeks develop cerebral palsy (CP) and 28% have severe motor disability. Those infants born extremely pre term (<28 weeks) cost the public sector £75835 (95% CI £27906–145508) per live birth not to mention the emotional cost to the family. To prolong gestation is therefore the suggested goal: however how and why might we delay birth in those at risk?